Methodological approaches to integrate gender analysis in One Health perspective at human-animal-ecosystem interface - Claudia Cataldo (CABI One Health)
Abstract The One Health approach considers the interdependence between environmental aspects, human and animal health, and promotes a multi-sectoral collaboration of policies, systems and processes that should be taken into account to prevent and mitigate emerging risks at human-animal-ecosystem interface. Gender is defined as the sum of roles and behaviors determined by the social context learned and adopted by men and women which lead to different identities and roles considered suitable for each of them. Men and women are systematically exposed to several factors that can affect their well-being; this exposure is influenced by gender, social rules and behaviors. It follows that gender analysis is an essential element to maximize the potential of One Health, and it is a lens to analyze, prevent and mitigate risks at the human-animal-ecosystem interface, more effectively, identifying in detail the target groups involved in specific contexts in a socio-ecological perspective. One Health impact statement The One Health approach to public health is a holistic approach that considers environmental sustainability, animal health, and human health together. Several factors including gender, age groups, cultures and social conditions may affect significantly the risk of diseases and their clinical evolution. Supplementing the One Health perspective with a gender analysis to study the Influence of social norms, activities, and risk behavior on exposure to infections, chemical pollution, and the consequences of climate change, could help to formulate targeted interventions and maximize the effectiveness of intersectoral approach at the human-animal-ecosystem interface. However, it is often ignored, but this inclusion is critical to the ongoing development of the One Health approach in prevention and preparedness to global threats in line with the recent socio-ecological principles.